Proposed Business Strategy Roadmap for Smart City Nusantara by Telkom Indonesia Toward Indonesian Urban Vision Year 2025 - Ashari, Panji; Toha, Mohamad (The Indonesian Journal of Business Administration, 2017)
Abstract - Problems arising from the city's high level of urbanization makes the solution to the problem of the city as a priority to be developed for the long-term needs. According to statistics, in 2014 Indonesia's population living in urban areas has reached more than 50% of the total population, the future is expected to reach 67% of the total population living in urban areas in Indonesia. Therefore, a solution is needed for the long-term development and smart city is one of the answer. Smart city is an urban concept based on ICT makes it possible to continue to be developed in accordance with the long-term needs in realizing the livable, equitable, independent, and competitive city in a sustainable manner for the welfare of urban communities, according to the character and potential of local culture as set forth in Vision Urban Indonesia 2025. The methodology research of this final project conducted was a descriptive qualitative research using primary and secondary data. Frontal attack is the recommended business strategy to win the market and competition smart city in Indonesia. Whereas the proposed tactics are Key Factors for Success to act appropriately, effectively, and efficiently. Frontal attack and Key Factors for Success then allocated  in activity mapping and then proceed to business model canvass and roadmap.Key words: Smart City Nusantara, Telkom Indonesia, business strategy, smart city, Indonesia